2023
DOI: 10.3390/jof9030385
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole Inhibits Histoplasma capsulatum In Vitro Growth and Decreases Mitochondrion and Cytoskeleton Protein Levels

Abstract: Histoplasmosis is a frequent mycosis in people living with HIV/AIDS and other immunocompromised hosts. Histoplasmosis has high rates of mortality in these patients if treatment is unsuccessful. Itraconazole and amphotericin B are used to treat histoplasmosis; however, both antifungals have potentially severe pharmacokinetic drug interactions and toxicity. The present study determined the minimal inhibitory and fungicidal concentrations of mebendazole, a drug present in the NIH Clinical Collection, to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
2
0
0
Order By: Relevance
“…Some studies have demonstrated antifungal activity of benzimidazoles such as flubendazole [65], albendazole [66], and mebendazole [35] against Cryptococcus neoformans, fenbendazole [67] against Cryptococcus gattii and C. neoformans, albendazole against Aspergillus spp. [68], and, more recently, mebendazole against Histoplasma capsulatum [49]. Similarly, our findings demonstrated antifungal activity in a group of anthelmintic benzimidazoles against CBM agents, suggesting potential targets for the development of new broad-range antifungal drugs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some studies have demonstrated antifungal activity of benzimidazoles such as flubendazole [65], albendazole [66], and mebendazole [35] against Cryptococcus neoformans, fenbendazole [67] against Cryptococcus gattii and C. neoformans, albendazole against Aspergillus spp. [68], and, more recently, mebendazole against Histoplasma capsulatum [49]. Similarly, our findings demonstrated antifungal activity in a group of anthelmintic benzimidazoles against CBM agents, suggesting potential targets for the development of new broad-range antifungal drugs.…”
Section: Discussionsupporting
confidence: 78%
“…A collection of substances-NIH Clinical Collection-was used in this study to identify drugs with antifungal activity against several CBM agents, and therefore with repurposing potential for CBM. This collection has been previously tested on other fungi [35,48,49], and, as observed here, benzimidazoles were also found to have antifungal activity.…”
Section: Discussionsupporting
confidence: 55%